Sectoral Growth and the Distribution of Income across Ethnic Groups in Malaysia - Saari, Mohd Yusof (Journal of Income Distribution®, 2011)
The objective of this article is to examine the impact of growth in different production sectors on the distribution of income across ethnic groups in Malaysia. A multiplier decomposition technique for a socio-economic system, represented by a Social Accounting Matrix (SAM), is used to analyze the impacts. Results show that growth in all production sectors tends to increase inter-ethnic income inequality, in particular for households in rural areas. Income inequality can be explained by differences in the payments per employed household across production sectors.